Analisis Pengaruh Genangan Air Lingkungan Pada Pelaksanaan Proyek Hotel Harris & Pop! Solo Terhadap Biaya (Studi Kasus Proyek Hotel Harris & Pop! Solo) - Darwanto, Dedi, Ir. H. Muhammd Nur Sahid, MM., MT, Jaji Abdurrosyid, ST., MT (2016)
With more hotel building in Solo caused a little bit space for hotel parking lot. Therefore need a place which adequate and function for parking lot in the hotel building. Basement is one of alternative way which function as parking lot. In the making of basement need a process excavation with certain elevation under ground surface. Generally the problem which appear in excavation implementation in making of basement is ground water existence at excavation area. One of technique to keep excavation area in dry condition with using groundwater control system or dewatering. Dewatering method which be used is predrainage and open pumping . Predrainage method working with use submersible pump which pump 1035,2 litre of water mean while open pumping method working with soak pump which pump debit water plan as 1684,80 litre/minute. Total cost analysis of dewatering is Rp 454.896.604,00 and calculation of total cost from contractor is Rp 483.400.000,00